2018
DOI: 10.1039/c8cp06264a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic arrest of front transformation to gain access to the bulk glass transition in ultrathin films of vapour-deposited glasses

Abstract: Capping as an strategy to improve thermal stability of ultrastable glasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…From that moment, many other techniques have been used to identify and investigate the dynamics of the liquid front. In all cases, results were consistent, showing as solid observations the non-dependence of front velocity with film thickness, for films thinner than the cross-over length, and a strong dependence of this velocity with temperature [30,99,106,117,173,175,[179][180][181]]. An empirical relation between velocity and temperature was suggested, where the relaxation time of the equilibrated super-cooled liquid is invoked to introduce the temperature dependence of the propagation front [120]:…”
Section: Front Meltingsupporting
confidence: 61%
See 2 more Smart Citations
“…From that moment, many other techniques have been used to identify and investigate the dynamics of the liquid front. In all cases, results were consistent, showing as solid observations the non-dependence of front velocity with film thickness, for films thinner than the cross-over length, and a strong dependence of this velocity with temperature [30,99,106,117,173,175,[179][180][181]]. An empirical relation between velocity and temperature was suggested, where the relaxation time of the equilibrated super-cooled liquid is invoked to introduce the temperature dependence of the propagation front [120]:…”
Section: Front Meltingsupporting
confidence: 61%
“…Most of the work on ultrastable glasses has involved molecular glasses. Since the first measurements in 2007 [1] with 1,3-bis-(1-naphthyl)-5-(2-naphthyl)benzene (TNB) (T g = 347 K) and indomethacin (IMC) (T g = 315 K), more than 45 different organic molecules, ranging from small molecules such as toluene [26][27][28] and ethylbenzene [28] to pharmaceuticals such as IMC and TNB and more recently to organic semiconductors like TPD [29,30], NPD [31,32] and TPBi [2], have shown their ability to form highly stable glasses upon growth by physical vapor deposition at the right processing conditions. Table 1 shows a comprehensive list of molecules and some of the outstanding properties of the vapor-deposited thin film ultrastable glasses obtained from them.…”
Section: Organic Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…We explain this behavior by faster crystal nucleation and growth at the free surface, aided by the higher mobility of surface molecules with respect to bulk molecules . Additionally, covering the bare surface of the emission layers may suppress the propagation of mobility fronts as has been observed for similar structures …”
Section: Methodsmentioning
confidence: 52%
“…In vapor-deposited toluene, it has been shown that decreasing the film thickness from 70 to 5 nm can increase the thermodynamic stability but decrease the apparent kinetic stability (5,6). In contrast, thin films covered with a top layer of another material do not show a significant evidence of reduced kinetic stability (21), indicating the nontrivial role of mobility gradients in thermal and kinetic stability.…”
mentioning
confidence: 99%